2021
DOI: 10.1108/intr-01-2021-0078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of media multitasking on executive function in adolescents: behavioral and self-reported evidence from a one-year longitudinal study

Abstract: PurposeThe longitudinal impact of media multitasking on the development of executive function has been understudied, as most of the existing studies are cross-sectional. This longitudinal study addresses this research gap and uses multiple measures, i.e. behavioral and self-reported, to explore the impact of media multitasking on the executive function of Chinese adolescents.Design/methodology/approachThis study followed 99 Chinese adolescents (Mage = 14.41, SD = 1.10; 42 boys and 57 girls) for one year using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…According to the scattered attention hypothesis, people who engage in media multitasking more frequently possess lower levels of cognitive abilities than those who less often engage in media multitasking (e.g., Müller et al 2021;Ophir et al 2009). Consistent with this hypothesis, research shows that heavy multitaskers (HMMs) exhibited worse performance on tasks of executive functions, including updating (Luo et al 2022), inhibition (Baumgartner et al 2014;Murphy and Creux 2021), and shifting (Ophir et al 2009) in comparison to light media multitaskers (LMMs). In a seminal study, Ophir et al (2009) grouped participants to HMMs (1 SD or more above the mean) and LMMs (1 SD or more below the mean), and assessed their capacities of updating, shifting, and inhibition.…”
Section: Media Multitasking and Cognitive Abilitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the scattered attention hypothesis, people who engage in media multitasking more frequently possess lower levels of cognitive abilities than those who less often engage in media multitasking (e.g., Müller et al 2021;Ophir et al 2009). Consistent with this hypothesis, research shows that heavy multitaskers (HMMs) exhibited worse performance on tasks of executive functions, including updating (Luo et al 2022), inhibition (Baumgartner et al 2014;Murphy and Creux 2021), and shifting (Ophir et al 2009) in comparison to light media multitaskers (LMMs). In a seminal study, Ophir et al (2009) grouped participants to HMMs (1 SD or more above the mean) and LMMs (1 SD or more below the mean), and assessed their capacities of updating, shifting, and inhibition.…”
Section: Media Multitasking and Cognitive Abilitiesmentioning
confidence: 94%
“…A complication to the situation is that a number of studies reported no relation between the frequency of media multitasking and cognitive abilities ( Van der Schuur et al 2015 ). Specifically, LMMs do not differ from HMMs in updating ( Edwards and Shin 2017 ), inhibition ( Luo et al 2022 ; Müller et al 2021 ; Ophir et al 2009 ), shifting ( Baumgartner et al 2014 ; Luo et al 2022 ; Minear et al 2013 ; Müller et al 2021 ), and reasoning ( Loh and Lim 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the impacts of media multitasking on cognitive measures are strongly contested and directionally inconsistent (e.g., Luo et al, 2021Luo et al, , 2022Murphy & Shin, 2022;Parry & Le Roux, 2021;Schneider & Chun, 2021;Wiradhany & Nieuwenstein, 2017), when reported, such effects tend to selectively impact switch costs and not laboratory stability indexes (e.g., Alzahabi & Becker, 2013;Ophir 13 et al, 2009;Wiradhany & Nieuwenstein, 2017). A similar pattern appears when using self-report flexibility and stability as opposed to task-based measures: Reported flexibility, but not stability, differs based on media multitasking (Luo et al, 2022).…”
Section: Individual Difference Variables Modulating Flexibility Do No...mentioning
confidence: 96%
“…Many university students are nowadays suffering from mental fatigue and stress caused by busy and competitive daily activities [ 1 , 2 ], learning with highly cognitive demanding tasks [ 3 , 4 ], and extensive use of digital devices in their daily work [ 5 , 6 , 7 , 8 , 9 , 10 ]. Research shows that exposure to natural environments has substantial benefits for improving psychological well-being (e.g., positive effect) and cognitive performance (e.g., working memory) [ 11 , 12 , 13 , 14 , 15 , 16 ], which have the potential to improve learning performance.…”
Section: Introductionmentioning
confidence: 99%